The influence of Educational Game Media on Kinesthetic Learning Styles in Early Childhood - AlAyyubi, IbnuImam; Masfuroh, AiSri; Maryati, Yati; Nurhikmah, Nurhikmah; Rahmawati, Siti (Iftitiah: Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2025)
This study aims to examine the impact of the use of educational game media on kinesthetic learning styles in early childhood. The study uses a quantitative research method with an explanatory research approach. The research was conducted at RA Al-Jazila with a population of 99 students and a sample size of 20 from class B4. The sampling technique used was probability sampling with simple random sampling, while the instruments used were questionnaires and tests. The data analysis requirement tests included normality testing using the Kolmogorov-Smirnov test and linearity testing, with hypotheses tested using correlation and regression analysis assisted by SPSS version 26. This study concludes that Educational Game Media has a significant effect on Kinesthetic Learning Styles in Early Childhood. Therefore, the use of educational game media is highly recommended in early childhood education, especially to support kinesthetic learning styles. This study also provides recommendations for teachers, educational institutions, and future researchers to develop innovations in the use of educational game-based learning media. Future researchers could explore more specific types of educational games or integrate digital technologies to improve learning effectiveness.